Peripheral Vision in Dyslexics - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
Scientists from the Research Laboratory of Electronics and the Departments of Biology, Electrical Engineering, and Computer Science at M.I.T. Cambridge, Mass. have collaborated in an investigation of the peripheral and foveal (central) vision of 5 dyslexic adult subjects compared to 5 normal readers.